A COMBINED MOLECULAR-GENETIC RISK SCORE FOR PREDICTING LIVER CIRRHOSIS IN CHRONIC HEPATITIS C: DEVELOPMENT AND CLINICAL VALIDATION (World Conference on Social Sciences, Law and Public Policy, 2026)
Liver cirrhosis (LC) develops in 15-30% of chronic hepatitis C (CHC) patients over 20-30 years, yet the trajectory of fibrosis progression varies substantially between individuals [1]. While clinical risk factors (age, alcohol use, HCV genotype) contribute to this variability, host genetic polymorphisms are now recognised as independent modulators of fibrosis kinetics. As R. Bataller and D.A. Brenner stated, "identifying patients at high risk of fibrosis progression remains the central unmet need in hepatitis C management, and genetic profiling represents the most promising avenue for this purpose" [2]. Despite extensive international data, a validated multi-locus genetic risk score integrated with clinical and instrumental parameters had not been developed for the Uzbek CHC population.